Stress-altering anterior insular cortex activity affects risk decision-making behavior in mice of different sexes - Shi, Tianyao; Feng, Shufang; Zhou, Zhonglin; Li, Fengan; Fu, Yuan; Zhou, Wenxia (Frontiers in Cellular Neuroscience, 2023)
Stress can affect people's judgment and make risky decisions. Abnormal decision-making behavior is a core symptom of psychiatric disorders, such as anxiety, depression and substance abuse. However, the neuronal mechanisms underlying such impairments are largely unknown. Anterior insular cortex (AIC) is a key structure to integrate sensory information with emotional and motivational states. These properties suggest AIC has the capacity to influence a subjective prediction in decision making. In this study, we demonstrated that stressed mice prefer to take more risky choices than control mice by using a gambling test. Manipulating neural activity of AIC or selectively inhibiting AIC-BLA pathway with chemogenetic intervention resulted in alterations of risk decision-making in mice. Different sexes may have different decision-making strategies in risky situations. Endogenous estrogen levels affect emotional cognition through modulating the stress system function in women. We observed decision-making behavior in mice of different sexes with or without stress experience. The result showed that female mice did not change choice strategy with increasing risk/reward probability, and preformed lower risk preference than male mice after stress. Using pharmacological method, we bilateral injected estrogen receptors (ERs) antagonist resulted in more risky behavior and decreased synaptic plasticity in AIC of female mice. Our study suggest that AIC is a crucial region involved in stress induced alteration of decision-making and estrogen in the AIC may regulate decision-making behavior via regulating synaptic plasticity.